A Comparative Study of Two Internationally Renowned Trombonists: Professors Fabrice Millischer and Irvin Wagner - Piguet-Persello, Delphine (My University, 2020)
While incredible natural abilities, talent, energy, determination, stamina, hard work, and luck are crucial for any musician interested in having an internationally successful career, other elements play key roles in finding success as well. This document specifically examines cultural aspects, choices, and practices that increase the likelihood of achieving an international career as a trombonist via the investigation of two internationally accomplished trombone players: Professors Fabrice Millischer and Irvin Wagner. This study aims to provide suggestions on how to achieve international acclaim for any aspiring trombonist through interviews and analysis of the triangulated data.
Keywords: Trombonist; Trombone; International Music Career; Fabrice Millischer; Irvin Wagner; Music Professor; Performance Philosophy; Music Teaching Philosophy